Effect of air temperature, milk production and shearing on drinking water intake of Angora goats in pen during summer - Calianno, Martin; Castillo, Daniel Alejandro; Hurtado, Santiago Ignacio; Deluchi, Saul Gaston; Garcia Falabella, Brenda Marilyn; Villar, Maria Laura; Villagra, Edgar Sebastian; Easdale, Marcos Horacio (Elsevier, 2025)
This study determines daily drinking water intake of Angora goats in pen during summer in North Patagonia (Argentina) and proposes a parametric equation predicting water intake in these conditions. Environmental and physiological parameters are also measured: dry matter intake, water in feed, animal weight, air temperature, shearing and milk production. Water intake varied from 1.8 to 5.5 L/goat/day. During lactation, the average was 3.9 L/goat/day. After weaning it was 3.3 L/goat/day. Then, after shearing, the average decreased to 2.5 L/goat/day. Equations from the literature taking into account body weight and milk production are the ones that best fits observed water intake values for our case study. We propose an equation that takes into account the effect of shearing, maximum daily air temperature (Tmax) and daily milk production. It shows the best fit with observed water intake time series. The study showed the sensitivity of goats’ water requirements during the summer as measured by a positive response to air temperature and downward requirement after both weaning and shearing management decisions. These results highlight the relevance of considering both environmental parameters and herd management decisions in the evaluation of water requirements of animals in pens, when body weight and feed intake remains nearly constant.